DIGITAL FINANCIAL LITERACY AND MSME PERFORMANCE IN THE PLATFORM ECONOMY: AN INTEGRATIVE CONCEPTUAL REVIEW - Nia Riana; Ijang Faisal (Organisasi Kreatif Indonesia Emas, 2024)
Background: The rapid expansion of digital payments, mobile banking, fintech platforms, online marketplaces, and data-driven financial services has changed the financial environment in which micro, small, and medium enterprises (MSMEs) operate. Access to digital finance can lower transaction frictions and widen financial inclusion, but effective use depends on the ability of owner-managers to understand financial information, evaluate digital products, manage risk, and integrate digital financial tools into business decisions. Aims: This article develops an integrative conceptual framework explaining how digital financial literacy can influence MSME performance through financial decision quality, digital-finance access and use, financial behaviour, and organizational capability. Research Method: The study uses an integrative conceptual review of verified peer-reviewed and institutional literature on financial literacy, digital financial literacy, digital finance, financial inclusion, fintech adoption, and SME performance. It does not claim a systematic-review sample size or empirical estimates that were not independently collected. Results and Conclusion: The synthesis suggests that digital financial literacy is most valuable when it improves the quality of financial decisions and enables productive, safe, and strategic use of digital finance. Access alone is insufficient. Financial behaviour, digital-finance accessibility, trust, cybersecurity awareness, and institutional support shape whether digital financial tools translate into stronger cash-flow management, financing capacity, operational efficiency, and business sustainability. Contribution: The paper proposes a capability pathway that distinguishes knowledge from effective use and performance outcomes, while integrating financial literacy and digital-finance perspectives into a practical framework for MSMEs and ecosystem actors.